2022
DOI: 10.3390/agriculture12111930
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cultivar, Processing and Storage on the Mycobiota of European Chestnut Fruits

Abstract: Sweet chestnut fruits are popular fruits commercialized as fresh or processed ready-to-eat products. The major post-harvest problems associated with stored chestnut fruits are fungal rots, which cause major losses in fruit quality. The aims of this work were to determine the incidence, abundance and diversity of rots and fungi in three chestnut varieties (Longal, Judia and Martaínha) of Portugal, collected from an industrial plant, and to identify the stages of storage and processing where fungi and rots are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…This fungus has now been isolated, identified, characterized and reported in chestnuts from the United Kingdom [17], United States of America [18], Chile [19], Spain [20], Ireland [21] and Turkey [22]. In Portugal, the first reports of the isolation of G. smithogilvyi from pre-harvest chestnuts were in 2017 [23] and in 2021 [24], and in post-harvest chestnuts in 2019 [25]. Although no extensive surveys about the incidence of G. smithogilvyi have been carried out in Portugal, Rodrigues et al [25] reported a 6.4% incidence in stored chestnuts that had already been visually selected, with rejected chestnuts showing as much as 40% infection.…”
Section: Introductionmentioning
confidence: 99%
“…This fungus has now been isolated, identified, characterized and reported in chestnuts from the United Kingdom [17], United States of America [18], Chile [19], Spain [20], Ireland [21] and Turkey [22]. In Portugal, the first reports of the isolation of G. smithogilvyi from pre-harvest chestnuts were in 2017 [23] and in 2021 [24], and in post-harvest chestnuts in 2019 [25]. Although no extensive surveys about the incidence of G. smithogilvyi have been carried out in Portugal, Rodrigues et al [25] reported a 6.4% incidence in stored chestnuts that had already been visually selected, with rejected chestnuts showing as much as 40% infection.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, chestnuts have various health benefits such as lowering cholesterol, preventing obesity and diabetes, fighting tumours, and improving the immune system ( Li et al, 2022a ). However, chestnut fruit is prone to rot and deteriorate during the harvest and storage periods because of high moisture content and rich nutrients, thus seriously affecting their quality and production value ( Rodrigues, Driss, Gomes-Laranjo, & Sampaio, 2022 ). At present, approximately >50% of chestnut production loss is caused by rot and deterioration during storage and transportation ( Vettraino et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…is the most commonly isolated genus in European sweet chestnuts ( Castanea sativa ) and American chestnuts ( Castanea americana ). Alternaria sp., Mucor sp., Rhizopus sp., and other pathogenic fungi are also prevalent ( Rodrigues et al, 2022 ). In Asia, common pathogenic fungi include Alternaria sp., Fusarium sp., Parvum sp., Trichothecium sp., Penicillium sp., Ozonium sp., Aspergillus sp., Colletotrichum sp., and Nigrospora sp ( Jiang & Tian, 2019 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no field treatments in Portugal being used to control fruit rots, and chestnut orchards are generally conducted under biological production systems. In contrast, several post-harvest methods are used for chestnut insect and fungal control, such as sterilising hydrothermal baths (48-50 • C) for 45 min, followed by cooling and drying [9], and water curing ('curatura') consisting of treatments in cold water (14-18 • C) for 7-9 days with or without the addition of biocontrol agents or their metabolites [10]. Rodrigues et al reported reduced contamination in chestnuts submitted to the traditional industrial hydrothermal bath (48 • C, 45 min), but the process was still not fully efficient against fungi [9].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several post-harvest methods are used for chestnut insect and fungal control, such as sterilising hydrothermal baths (48-50 • C) for 45 min, followed by cooling and drying [9], and water curing ('curatura') consisting of treatments in cold water (14-18 • C) for 7-9 days with or without the addition of biocontrol agents or their metabolites [10]. Rodrigues et al reported reduced contamination in chestnuts submitted to the traditional industrial hydrothermal bath (48 • C, 45 min), but the process was still not fully efficient against fungi [9]. For the storage of chestnuts, researchers tested the use of hot air assisted radio frequencies [11], electron-beam radiation [12], and ozonation [13], among others, with limited success regarding reducing contamination.…”
Section: Introductionmentioning
confidence: 99%